Design state exploration applied to the development of a remote lab for projectile launch experiments - Alves, Gustavo R. (2013)
This paper describes the application of Design State Exploration techniques in the development of a remote lab for projectile motion experiments. The application was enabled by the existence of two independent teams: one composed of a series of internships that started first and another with two grantees that started a few months later. The paper presents evidence on how this approach provided gains in the development process conducted by the second team that benefited from design state exploration studies performed by the first team. This particular aspect is highlighted in relation to the work already presented in the 10th Remote Engineering and Virtual Instrumentation (REV) conference.